PENGGUNAAN GLASGOW OUTCOME SCALE DALAM PENILAIAN KONDISI PASIEN PASCA CEDERA KEPALA - Suwaryo, Putra Agina Widyaswara; Yuwono, Podo (LPPM STIKES MUHAMMADIYAH GOMBONG, 2017)
The incidence of disability as outcomes in head injury patients reaches 5.3 million people per year. Disability occurring is 1 year after injury. Glasgow Outcome Scale or GOS is a scoring or instrument used to assess patients ranging from 1 to 12 months after head injury. GOS was first created in 1975 by Bryan Jennett and Michael Bond, who have over 40,000 citations and is the most widely cited article in research on head injuries. GOS is also further developed into GOS-E or Glasgow Outcome Scale - Extended and GODS or Glasgow Outcome Discharge Scale. The purpose of this study was to determine the level of validity and reliability of GOS in assessing the condition of head injury patients. This study was a descriptive observation of 112 head injury patients measured using GOS for 6 months post injury. The result of the research showed that the characteristics of respondents with the average age of 18-40 years were 58.9% productive), male was 75.8%, the last level of senior high school was 35.7%, farmers, traders and laborers were 39.2% of 65.1% and GCS 3-8 value of 49.1%. The level of validity with the value of count> 0.195 with 95% CI and reliability is very high with correlation coefficient value> 0.8. Therefore, GOS is a scoring that can be used to assess the outcome of head injury patients by maintaining good clinical and nursing care at home or rehabilitation phase well.Key word : Glasgow Outcome Scale, Head Injury, Reliability, Validity